PENCABUTAN PENGADUAN PADA KASUS TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA BERDASARKAN PASAL 75 KITAB UNDANG-UNDANGHUKUM PIDANA DIKAITKAN DENGAN KEADILAN RESTORATIVE JUSTICE (STUDI KASUS KEPOLISIAN SEKTOR TAMPAN PEKANBARU) - Iis Fatmala Sari; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Domestic violence is not a new thing, but it is a crime that has long been rooted in the culture of society. As set forth in Article 51 to Article 53 of Law Number 23 Year 2004 on the Elimination of Domestic Violence is a complaint offense, in which the victim can determine whether the case has been reported to be terminated and revoked by his complaint or will continue until before the demand is read out at Court. In some cases of domestic violence that often ends in the settlement of cases Domestic Violence ends a verdict for the imposition of a prison sentence to the perpetrator.Based on the background of the problems that the authors describe above, the authors are interested to conduct research with the title: